An Investigation of Education for Sustainable Development (ESD) Implementation in Lao Teacher Education Institutions (Lao TEIs) through Academic Workshop - VATHANAVONG , Thongtiane; PHANHNALATH, Vikate; SAN, Somepheth; VATHANAVONG , Phaivanh; KHOTSAIGNO, Saiphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This research attempted to investigate the implementation of Education for Sustainable Development (ESD) at Teacher Education Institutions (TEIs) in Lao PDR through Academic Workshop. The objectives of this research were to investigate understanding the concepts of ESD, skills and attitudes to contribute to ESD before and after the workshop, ESD Promotion, capacity building in implementing ESD and creating professional networks within Lao TEIs. The subject of the study comprised of 30 educators, who have actively involved in a wide range of ESD workshops, which are held nationally and internationally. The key educators were from education faculties such as Souphanouvong University, National University of Laos and other three Teacher Training Colleges from Northern part of Laos, who attended the ESD workshop in academic year 2017-18. The principal instruments of this investigation were achievement test and comments record. The data then analyzed by mean, standard deviation, documentary analysis and t-test. The results of this research found that: The participants’ understanding the concept of ESD achieved the criteria by 70% with a statistical significance level at 0.01, the participants’ number who achieved the criteria was 86.6%. The context of ESD implementation in teacher education institutions is still in its beginning stage. To promote ESD, funding should be sufficiently allocated, there should be expert team, integrate ESD into the curriculum, setting clear strategic planning and policy in line with the regional and global ESD framework. As well as building capacity in TEIs by adapting ESD concept into curriculum content, which are interconnected with economic, political, socio-cultural and environmental aspects. Creating ESD professional network of Lao TEIs by exchanging and sharing activities to foster ESD in the same path.